Determinan audit delay dimoderasi reputasi Kantor Akuntan Publik - Jaya, Ratna Indra; Darminto, Dwi Prastowo; Rachbini, Widarto; Darmansyah, Darmansyah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Issuers' obligations contained in the Indonesia Stock Exchange in submitting audited financial reports must be in accordance with the time determined by the OJK institution. Companies that are not in trouble should submit financial statements that have been audited by an external audit in a timely manner, with no difference in time either at the date of the financial statements or the date of the audit opinion. This study aims to analyze the effects of the factors of the audit delay, namely firm size, audit committee, and the value of profitability on audit delay by moderating the reputation of the Public Accounting Firm (KAP). The secondary data used in this study are companies manufacturing the food and beverage sector from the Indonesia Stock Exchange (IDX) website and company websites from 2018 to 2020. The results of research on the audit committee and company size have an effect on audit delay, the reputation of the Public Accounting Firm does not moderate the audit committee and firm size on audit delay, profitability has no effect on audit delay, the reputation of the Public Accounting Firm does not create a moderation of profitability on audit delay.